Pendidikan Islam Dari Fenomena Viralnya Youtuber Pak Ndul: Local Genius Ahlinya Ahli Dan Intinya Inti Dari Bojonegoro - Sofan Rizqi; Robingun Suyud El Syam; Ahmad Guspul; Adi Suwondo (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The viral phenomenon of local genius YouTuber Pak Ndul from Bojonegoro is interesting to study, since this research has never been studied before. The article intends to examine Islamic education from the viral phenomenon of YouTuber Pak Ndul: local genius, expert and essentially the core of Bojonegoro, using a phenomenological method, a qualitative approach, and descriptive analysis. The research results concluded; that creativity in packaging language is very important in order to attract other people. This also applies in Islamic education, that the delivery of material must be packaged as attractively as possible in order to convey the learning objectives. A spirit of curiosity must be put forward in order to overcome failure, which gives birth to a spirit of always learning in order to improve one's abilities. A deep religious understanding implies that religion requires a child to be filial to his parents. Research implications: the importance of hard work based on religious values. The study challenges other researchers to research further with a specific and in-depth scope.